The role of text messaging and telehealth messaging apps - Ganapathy, Sashikumar (2022)
This article focuses on the role of text messaging and messaging applications, discusses technical and legal issues, and reviews current examples of the application of text messaging in the clinical adult and pediatric practice. Reviews of current examples of text messaging in adult and pediatric practice show uptake has been increasing substantially in recent years. In pediatric care text messaging has been used for behavior intervention and outcomes tracking. Although applications are promising, the potential of nonsynchronic messaging in the formal delivery of care is still in the neonatal phase compared with its grown-up existence in day-to-day modern life.